Canada at a crossroad: The imperative for realigning ocean policy with ocean science. (January 2016) - Bailey, Megan; Favaro, Brett; Otto, Sarah P.; Charles, Anthony; Devillers, Rodolphe; Metaxas, Anna; Tyedmers, Peter; Ban, Natalie C.; Mason, Taylor; Hoover, Carie; Duck, Thomas J.; Fanning, Lucia; et al.
Abstract: Canada's ocean ecosystem health and functioning is critical to sustaining a strong maritime economy and resilient coastal communities. Yet despite the importance of Canada's oceans and coasts, federal ocean policy and management have diverged substantially from marine science in the past decade. In this paper, key areas where this is apparent are reviewed: failure to fully implement the Oceans Act, alterations to habitat protections historically afforded under Canada's Fisheries Act, and lack of federal leadership on marine species at risk. Additionally, the capacity of the federal government to conduct and communicate ocean science has been eroded of late, and this situation poses a significant threat to current and future oceans public policy. On the eve of a federal election, these disconcerting threats are described and a set of recommendations to address them is developed. These trends are analyzed and summarized so that Canadians understand ongoing changes to the health of Canada's oceans and the role that their elected officials can play in addressing or ignoring them. Additionally, we urge the incoming Canadian government, regardless of political persuasion, to consider the changes we have documented and commit to aligning federal ocean policy with ocean science to ensure the health of Canada's oceans and ocean dependent communities. Highlights: Canada's ocean policy has diverged from ocean science in the past decade. Canada's government has no fully implement key pieces of ocean legislation. Erosion in government science capacity and communication jeopardizes ocean policy. Canada's incoming government should commit to restoring habitats to the Fisheries Act . A scientific integrity policy to improve communication transparency should be adopted.